How Accurate Are the Imf's Short-Term Forecasts? : Another Examination of the World Economic Outlook - Artis, Michael (IMF Working Papers; Working Paper ;, 1996)
This paper analyzes the short-term forecasts for industrial and developing countries produced by the International Monetary Fund, and published twice a year in the World Economic Outlook (WEO). For the industrial country group, the WEO forecasts for output growth and inflation are satisfactory and pass most conventional tests in forecasting economic developments, although forecast accuracy has not improved over time, and predicting the turning points of the business cycle remains a weakness. For the developing countries, the task of forecasting movements in economic activity is even more difficult and the conventional measures of forecast accuracy are less satisfactory than for the industrial countries.